Hybrid Ablation: a Future Development Trend in the Management of Atrial Fibrillation - ZHANG Ning, HOU Ming, MEI Bo, JIN Weitao, TAN Xiong, YANG Mingchuan, WANG Liang, LIU Yong, LAI Yinglong (Zhongguo quanke yixue, 2023)
As the most common type of arrhythmia, atrial fibrillation has proven to be associated with serious adverse cardiovascular and cerebrovascular events, such as heart failure, stroke and myocardial infarction. The global number of patients with atrial fibrillation has exceeded 33 million, and it is estimated to be more than doubled in the next 40 years. Although years of efforts have been made to the research on pathophysiological mechanism, and the exploration of new treatments and improvement of treatments regarding atrial fibrillation, the management of atrial fibrillation is still a difficult problem in clinical medicine, and there is no consensus on the best treatment and the choice of energy source for ablation in atrial fibrillation with the increasing advances made in surgical and catheter ablative techniques. Catheter ablation often requires multiple operations with unsatisfactory success rate and surgical ablation is often associated with high risk of postoperative adverse events. Hybrid ablation, a new treatment recently developed by the joint efforts of cardiac surgeons and electrophysiologists, integrates the merits of catheter ablation and minimally invasive surgical ablation but overcomes the limitations of the two, has proven to be effective in reducing the risk of postoperative adverse outcomes, and considerably efficacious in treating persistent atrial fibrillation, especially long-term persistent atrial fibrillation. We reviewed the advances in atrial fibrillation ablation, and comparatively analyzed existing studies of hybrid ablation, and summarized the advantages and challenges of this treatment, hoping to provide one more option for clinical treatment of atrial fibrillation.